INnovative Steroid Treatment to reduce Asthma development in children after first-time Rhinovirus-induced wheezing (INSTAR): protocol for a randomised placebo-controlled trial - Maria Vollsæter; Knut Øymar; Svein Arne Nordbø; Tytti Vuorinen; Kari Risnes; Claus Klingenberg; Tuomas Jartti; Henrik Døllner; Anna Partty; Håvard Ove Skjerven; Turid Follestad; Trude Elvebakk; et al. (BMJ Open)
Introduction Asthma is a leading cause of morbidity and healthcare use among children. Risk factors of childhood asthma include atopic predisposition and severe wheezing episodes caused by rhinovirus infection in early life. In children with first-time rhinovirus-induced wheezing, we aim to study the response of a short corticosteroid treatment to prevent recurrent wheezing and asthma.Method and analysis This is a double-blind, randomised, placebo-controlled, phase IV, international multicentre trial involving eight sites in Norway, Sweden and Finland. Two hundred and eighty 3–23 months old steroid-naïve children are randomised 1:1 to receive oral dexamethasone (0.3 mg/kg/day) versus placebo in 3 days for their first wheezing episode and rhinovirus infection. Rhinovirus is diagnosed with multiplex PCR. The two co-primary outcomes are time to next physician-confirmed wheezing episode, and time to asthma, within 24 months from inclusion. Asthma is defined as fulfilment of the 2007 National Asthma Education and Prevention Program—criteria for initiating asthma controller medication in children aged 0–4 years. Primary interaction analyses are age, gender, atopic predisposition, risk genotypes and viral co-detection. The optimal cut-off on the rhinovirus genome load used to define a true rhinovirus infection will be assessed by exploring interactions between rhinovirus genomic loads and study drug on the co-primary outcomes. Secondary outcomes are number of wheezing episodes, duration and severity of each wheezing episode, bronchial hyperreactivity, quality of life and safety (height/weight development) at 24 months from inclusion.Ethics and dissemination Rhinovirus positive children with acute wheezing fulfilling inclusion and exclusion criteria are enrolled after informed consent from both caregivers. This trial has received ethical approval from all sites. Results will be submitted to Competent Authorities and disseminated via peer-reviewed publications and conferences within paediatrics and other relevant fields. If proven effective, findings may be implemented directly into paediatric clinical guidelines.Trial registration number NCT03889743.